Working mothers: Resilience and subjective well-being - Prahara, Sowanya Ardi; Noviyanti, Refana (Insight: Jurnal Ilmiah Psikologi, 2023)
This study aims to determine the correlation between resilience and subjective well-being in working mothers. The method used in this study is a quantitative method with a correlational design. The subjects in this study amounted to 88 people with characteristics including a woman who is married and has children, works in the formal sector, and is at least 21 years old and a maximum of 60 years old. The data collection method in this study used two scales, namely the Subjective Well-Being Scale and the Resilience Scale. The data analysis technique used is the product-moment correlation from Karl Pearson. The results of the analysis of the data obtained provide a relationship coefficient value (rxy) of = 0.580 (p <0.05), which means that there is a significant positive correlation between resilience and subjective well-being.